Transcriptomic analysis of nitrogen metabolism pathways in Klebsiella aerogenes under nitrogen-rich conditions - Chen, Yanyan; Lin, Yijing; Zhu, Jingyi; Zhou, Jiayin; Lin, Haoyi; Fu, Yiting; Zhou, Yan (Frontiers in Microbiology, 2024)
The acceleration of the nitrogen cycle and the nitrogen excess observed in some coastal waters has increased interest into understanding the biochemical and molecular basis of nitrogen metabolism in various microorganisms. To investigate nitrogen metabolism of a novel heterotrophic nitrification and aerobic denitrification bacterium Klebsiella aerogenes strain (B23) under nitrogen-rich conditions, we conducted physiological and transcriptomic high-throughput sequencing analyses on strain B23 cultured on potassium nitrate–free or potassium nitrate–rich media. Overall, K. aerogenes B23 assimilated 82.47% of the nitrate present into cellular nitrogen. Further, 1195 differentially expressed genes were observed between K. aerogenes B23 cultured on potassium nitrate–free media and those cultured on potassium nitrate-rich media. Gene annotation and metabolic pathway analysis of the transcriptome were performed using a series of bioinformatics tools, including Gene Ontology, Kyoto Encyclopedia of Genes and Genomes, and Non-Redundant Protein Database annotation. Accordingly, the nitrogen metabolism pathway of K. aerogenes B23 was analyzed; overall, 39 genes were determined to be involved in this pathway. Differential expression analysis of the genes involved in the nitrogen metabolism pathway demonstrated that, compared to the control, FNR, NarK/14945, fdx, gshA, proB, proA, gapA, argH, artQ, artJ, artM, ArgR, GAT1, prmB, pyrG, glnS, and Ca1 were significantly upregulated in the nitrogen-treated K. aerogenes B23; these genes have been established to be involved in the regulation of nitrate, arginine, glutamate, and ammonia assimilation. Further, norV, norR, and narI were also upregulated in nitrogen-treated K. aerogenes B23; these genes are involved in the regulation of NO metabolism. These differential expression results are important for understanding the regulation process of key nitrogen metabolism enzyme genes in K. aerogenes B23. Therefore, this study establishes a solid foundation for further research into the expression regulation patterns of nitrogen metabolism–associated genes in K. aerogenes B23 under nitrogen-rich conditions; moreover, this research provides essential insight into how K. aerogenes B23 utilizes nutritional elements.